From Waqf, ancestor worship to the rise of the global trust: A history of the use of the trust as a vehicle for wealth transfer in Singapore - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2018)
This Article focuses on the migration of English trust law to Singapore and its past and present uses in relation to wealth transfer through the ages. In Singapore, trust law arrived together with the corpus of English law. Unlike criminal law, which was influenced by Indian codes promulgated by the English in British India, trust law was received into Singapore directly from England.